The effect of resistance band training on the speed of gyaku tsuki punches dojo hikari karate team - Yuhatanza, Shasi Novtri Miko; Kusdinar, Yopi; Sagitarius, Sagitarius; Mulyana, Mulyana (Jurnal Ilmu Keolahragaan, 2025)
Background. Speed as a physical element plays an important role that is used to hit, kick, parry, and others. there are still many athletes when hitting Gyaku Tsuki the punch is slow because the skills in hitting gyaku tsuki have not shown maximum performance, which is most likely influenced by a number of supporting factors that are still less than optimal. Objectives. The purpose of this study was to determine the effect of applying resistance band training on the speed of gyaku tsuki punches on Karateka Dojo Hikari Karate Team. Methods. The research design used is one group pre test- post test, The sample withdrawal in this study was using purposive sampling, namely the population taken was only male athletes totaling 10 male athletes in the Dojo Hikari Karate Team, with an average age of 15-18 years. The research instrument used was the Velocity Speed Gun. The data was processed and analyzed using the normality test with Shapiro-Wilk then analyzed using the independent t test with SPSS 23. Results. The results show a Sig value. (2-tailed) of 0.00, based on the test results, the value of Sig. (2-tailed)